THEOLOGIZING IN A WORLD OF PLURALISM - Coward, Harold G (Journal of Dharma, 1981)
In recent years theologians have concerned themselves with the challenges presented by science, secular society, marxism and technology. Today these important and continuing concerns must give place to the problems presented to the theologian by the face to face encounter of the world religions. Advance warning to this effect was given theologians some seventeen years ago by Wilfred Cantwell Smith.